The mediaeval temples at Sātgaon - Deglurkar, G. B., 1933- (Temples of the Vidarbha Region, 1973)
On the archaeology and architecture of a group of temples in Satgaon Village in Buldhana District of the Vidarbha Region of Maharashtra State.